2014
DOI: 10.1111/are.12411
|View full text |Cite
|
Sign up to set email alerts
|

Hollow sperm syndrome during spermatogenesis in the giant tiger shrimpPenaeus monodon(Fabricius 1798) from eastern Australia

Abstract: During spermatogenesis, giant tiger shrimp (Penaeus monodon) from Queensland, eastern Australia had a high proportion of testicular spermatids that appeared ‘hollow’ because their nuclei were not visible with the haematoxylin and eosin stain. When examined by transmission electron microscopy, the nuclei of hollow spermatids contained highly decondensed chromatin, with large areas missing fibrillar chromatin. Together with hollow spermatids, testicular pale enlarged (PE) spermatids with weakly staining and marg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Poor reproductive potential of domesticated Penaeus monodon broodstock has been a major hurdle to the expansion of aquacultural production in this species (Kumar & Engle, ). Reproductive issues for the male P. monodon broodstock in captivity include abnormal spermatogenesis (Chong et al, ), a lack of mating behavior (Marsden, Richardson, Mather, & Knibb, ) and pathological changes in the reproductive tract (Chamberlain, Johnson, & Lewis, ); consequently, a better understanding of basic male reproductive biology including spermatogenesis, post‐testicular sperm maturation and spermatophore formation is fundamental and critical to addressing these reproductive problems in aquaculture.…”
Section: Introductionmentioning
confidence: 99%
“…Poor reproductive potential of domesticated Penaeus monodon broodstock has been a major hurdle to the expansion of aquacultural production in this species (Kumar & Engle, ). Reproductive issues for the male P. monodon broodstock in captivity include abnormal spermatogenesis (Chong et al, ), a lack of mating behavior (Marsden, Richardson, Mather, & Knibb, ) and pathological changes in the reproductive tract (Chamberlain, Johnson, & Lewis, ); consequently, a better understanding of basic male reproductive biology including spermatogenesis, post‐testicular sperm maturation and spermatophore formation is fundamental and critical to addressing these reproductive problems in aquaculture.…”
Section: Introductionmentioning
confidence: 99%
“…The inferior reproduction performance of domesticated broodstock of P. monodon has been regarded as one of the prioritized issues for the nauplii production in the prawn aquaculture hatcheries (Browdy, 1998). Although the female domesticated broodstock were believed to be major contributor of poor reproductive outcome (Arnold et al, 2013;Coman et al, 2006), recent studies have also shown the reproductive performance of male broodstock were similarly undermined by the process of domestication (Alfaro-Montoya, 2010;Chong et al, 2015;Parnes et al, 2007). For this case, the level of SDF may be considered as a potential parameter, for which the relative reproductive capacity of selected male broodstock could be assessed; the selection of genetic lines of males exhibiting low levels of SDF could then be the basis of improvements in reproductive efficiency within the prawn aquaculture.…”
Section: Discussionmentioning
confidence: 99%
“…Ten sexually mature male P. monodon showing no melanization in the gonopores were euthanized in an ice water slurry for 10 min (Thompson et al, 2010) and their reproductive organs were dissected out. The left side of the reproductive organ was fixed in Davidson's solution (1 L contains 220 mL 37-40% formaldehyde, 330 mL 95-100% ethanol, 115 mL glacial acetic acid, 335 mL distilled water, pH 3.5-4.0) for 24 h at room temperature and then transferred to a 70% ethanol solution (Chong et al, 2015) for histological study, whereas the right side was preserved in the crustacean reproductive fixative (2% paraformaldehyde, 2.5% glutaraldehyde in 0.1 M sodium cacodylate with 5% sucrose, pH 7.6) at 4 °C for 24 h (Ro et al, 1990) for transmission electron microscopic study.…”
Section: Sample Preparationmentioning
confidence: 99%
See 2 more Smart Citations